A Study on the Impact of Recruitment and Selection Processes on Employee Hiring Performance - Jyothika, Dasini; Sankar Ganesh, R (Shanlax International Journal of Management, 2025)
This study examines the impact of recruitment and selection processes on employee hiring performance within organizations. The objective was to evaluate existing recruitment and selection policies, identify associated challenges, and propose strategies to enhance human resource planning and development. Data was collected through questionnaires administered to 120 organizational staff members. The findings revealed that common recruitment methods include public job advertisements, employment agencies, and campus recruitment. However, the study also highlighted several challenges such as lack of transparency, limited reach, and inefficiencies in candidate evaluation. It was recommended that organizations ensure fairness and consistency throughout the recruitment process and conduct regular performance appraisals to enhance employee development. An effective and fair recruitment system not only leads to higher job satisfaction and motivation among employees but also strengthens the organization’s competitive edge in the industry.